2004
DOI: 10.4315/0362-028x-67.11.2570
|View full text |Cite
|
Sign up to set email alerts
|

Home Storage Temperatures and Consumer Handling of Refrigerated Foods in Sweden

Abstract: The lack of data on consumer refrigeration temperatures and storage times limits our ability to assess and manage risks associated with microbial hazards. This study addressed these limitations by collecting data on temperatures and storage handling practices of chilled foods. Consumers from 102 households in Uppsala, Sweden, were instructed to purchase seven food items (minced meat, fresh herring fillets, soft cheese, milk, sliced cooked ham, vacuum-packed smoked salmon, and ready-to-eat salad) and to store t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
4
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 16 publications
10
80
4
4
Order By: Relevance
“…Similar to our study, the most important factors for choosing foods were: freshness, the expiry date, and safety assurance (28,30,37). Food Safety, Preparation and Storage: In agreement with our findings, respondents of other studies (11,38,39) also stated incorrect temperature of the refrigerator. Temperature as key factor in the growth of microorganisms should be assessed in order to control the growth of psychotropic microorganisms (40) (recommended temperature is 4.4°C) (41).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our study, the most important factors for choosing foods were: freshness, the expiry date, and safety assurance (28,30,37). Food Safety, Preparation and Storage: In agreement with our findings, respondents of other studies (11,38,39) also stated incorrect temperature of the refrigerator. Temperature as key factor in the growth of microorganisms should be assessed in order to control the growth of psychotropic microorganisms (40) (recommended temperature is 4.4°C) (41).…”
Section: Discussionsupporting
confidence: 91%
“…Surveys indicated that incorrect distribution of raw and cooked foods in refrigerators may lead to crosscontamination (39,43). Separate and appropriate storage of raw and cooked foods and covered containers has been recommended in order to prevent the transferring of pathogens into the refrigerator (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…In an Australian telephone survey (Jay, Comar & Govenlock, 77 1999) only 15.5% of respondents knew the temperature of their fridge. A Swedish survey 78 (Marklinder et al, 2004) found a good level of awareness amongst its survey group, with 79 85% of respondents knowing the recommended refrigeration temperature (in this case 8°C). 80…”
Section: Introduction 22mentioning
confidence: 98%
“…However, retrospective analysis of foodborne disease outbreaks or cases provides limited information on consumer food safety-related behavior. The accuracy and availability of appropriate data/information can be limited because people often find it difficult to remember exact details regarding their own consumption of food and food handling practices, and such details can have a significant effect on disease occurrence (Marklinder et al, 2004;Janjic et al, 2015c). The ultimate purpose of consumer studies as related to foodborne disease is to determine what proportion of foodborne disease outbreaks are due to improper handling of food in households and to determine what consumers know about food safety and why some safe food handling practices are applied and some are not (Tucker et al, 2006).…”
Section: Consumer Awareness and Educationmentioning
confidence: 99%